Analysis of Difficulties of Blind Students (Low Vision) in Developing Critical Thinking Skills Through Problem Solving - Ina, Ina Agustin; Wiratsiwi , Wendri (Universitas Nusantara PGRI Kediri, 2024)
This study aims to describe the difficulties of blind students (low vision) in developing critical thinking skills through problem solving. This type of research is qualitative descriptive research. The subject of the study was one blind student with low vision. The place of research was in the PGSD study program, FKIP, PGRI Ronggolawe University Tuban. The research instrument was an observation sheet and interview to find out the initial problems about critical thinking skills, a test sheet instrument in the form of an essay of 6 questions which will later be used as a reference in describing the difficulties of low vision students in developing critical thinking skills. The assessment indicators refer to Facione. Explanation, inference and interpretation indicators are in the good category, analysis indicators get a low category, self-regulation and evaluation indicators are in the sufficient/moderate category. Based on the results of the analysis of the difficulties faced by students in developing critical thinking skills are 1) students have difficulty in determining alternatives to the problems given, 2) students have difficulty in choosing and solving problems related to inclusive education given by lecturers, 3) students are not used to solving problems related to critical thinking, this is because the form of exam questions applied to students is still memorization and memory, 4) students are less creative in choosing or finding the right strategy according to the problems given.